FINANCIAL PERFORMANCE ANALYSIS OF PT. CHITOSE INTERNASIONAL, Tbk 2017-2021 USING THE ECONOMIC VALUE ADDED MEASUREMENT - Dinatonia Jovery Matruty (Jurnal Ekonomi, 2023)
Generating profits alone is not enough to provide an overview of the financial performance of a good company, for that purpose this writing aims to know and analyze the financial performance of PT. Chitose International, Tbk in 2017-2021 using the Economic Value Added method which will provide an overview of added value for shareholders. The results of the analysis using economic value added show the financial performance of PT. Chitose Internasional, Tbk in 2017-2018 is not good because it has a negative EVA < 0 or negative EVA. This means that there is no increase in the value of the company to its owners by the company's management, this is possible because the increase in the company's net sales value is almost balanced with the cost of goods sold and other expenses. On the one hand, the cost of capital is greater than the company's ability to earn profits, and the value of NOPAT and Capital Charges in 2021 is even negative.